Prevalensi pneumonia pada anak - Dahlia, Dahlia; Ali, Yaumil Mutmainnah; Samosir, Abdi Dwiyanto Putra (Holistik Jurnal Kesehatan, 2026)
Background: Pneumonia is a leading cause of morbidity and mortality in children worldwide, contributing to 14% of global under-five deaths. In Indonesia, pneumonia is a leading cause of hospitalization in children, but specific epidemiological data at the hospital level is still limited. Purpose: To determine the characteristics of pediatric pneumonia patients based on age, sex, and type of pneumonia. Method: This descriptive study, using a cross-sectional design, was conducted at Ibnu Sina Hospital, Makassar, South Sulawesi, from November 2024 to January 2025. The sampling technique used was total sampling. Secondary data were obtained from medical records, including age, gender, and type of pneumonia. Descriptive analysis was performed using Microsoft Excel and SPSS by calculating frequency distributions and percentages. Results: Of the 410 patients, 222 respondents (54.1%) were predominant in the 1–5 years age group, followed by 109 respondents (26.6%) in the 6–12 years age group, 46 respondents (11.2%) in the 1–12 months age group, and 33 respondents (8.0%) in the 13–18 years age group. Males predominated with 219 respondents (53.4%), compared to females with 191 respondents (46.6%). The most common type of pneumonia was Community Acquired Pneumonia/CAP, with 228 respondents (55.6%), CAP with comorbidities with 137 patients (33.4%), and bronchopneumonia with 45 respondents (11.0%). Conclusion: Pneumonia in children most commonly occurs in the 1–5 years age group, with a male predominance, and CAP is the most common type. Suggestion: Hospitals can improve pneumonia prevention programs focused on high-risk age groups by educating parents about the importance of complete immunizations, exclusive breastfeeding, and avoiding environmental risk factors. Improved medical record keeping, making it more comprehensive and structured, is needed to support further research.   Keywords: Childhood Pneumonia; Community Acquired Pneumonia; Epidemiological Characteristics; Toddlers.   Pendahuluan: Pneumonia merupakan penyebab utama morbiditas dan mortalitas pada anak diseluruh dunia, menyumbang 14% kematian balita secara global. Di Indonesia, pneumonia menjadi salah satu penyebab utama rawat inap anak, namun data epidemiologi spesifik di tingkat rumah sakit masih terbatas. Tujuan: Untuk mengetahui gambaran karakteristik pasien anak pneumonia berdasarkan usia, jenis kelamin, dan jenis pneumonia. Metode: Penelitian deskriptif dengan desain cross-sectional, dilakukan di Rumah Sakit Ibnu Sina Makassar, Sulawesi Selatan,  pada periode November 2024 hingga Januari 2025. Teknik pengambilan sampel menggunakan metode total sampling. Data sekunder diperoleh dari rekam medis mencakup usia, jenis kelamin, dan jenis pneumonia. Analisis dilakukan secara deskriptif menggunakan Microsoft Excel dan SPSS dengan menghitung distribusi frekuensi dan persentase. Hasil: Dari 410 pasien, didominasi oleh kelompok usia 1–5 tahun sebanyak 222 responden (54.1%), diikuti 6–12 tahun sebanyak 109 responden (26.6%), 1–12 bulan sebanyak 46 responden (11.2%), dan 13–18 tahun sebanyak 33 responden (8.0%). Predominansi jenis kelamin laki-laki sebanyak 219 responden (53.4%) dibanding perempuan sebanyak 191 responden (46.6%). Jenis pneumonia tersering adalah Community Acquired Pneumonia/CAP sebanyak 228 responden (55.6%), CAP dengan penyakit penyerta sebanyak 137 pasien (33.4%), dan bronkopneumonia sebanyak 45 responden (11.0%). Simpulan: Pneumonia anak yang paling banyak terjadi pada kelompok usia 1–5 tahun dengan predominansi laki-laki, dan CAP merupakan jenis tersering. Saran: Pihak rumah sakit dapat meningkatkan program pencegahan pneumonia yang difokuskan pada kelompok usia berisiko tinggi melalui edukasi orang tua mengenai pentingnya imunisasi lengkap, ASI eksklusif, dan menghindari faktor risiko lingkungan. Diperlukan peningkatan kualitas pencatatan rekam medis yang lebih lengkap dan terstruktur untuk mendukung penelitian lanjutan.   Kata Kunci: Community Acquired Pneumonia; Karakteristik Epidemiologi; Pneumonia Anak; Usia Balita.